Affordances of video-based professional development for supporting physics teachers' judgments about evidence of student thinking. (November 2018) - Alonzo, Alicia C.; Kim, Jiwon
Abstract: This study explores the affordances of a video-based professional development workshop for supporting physics teachers' content-specific judgments about evidence of student thinking. We rated both the quality of teachers' discussions and the judgments that resulted as they discussed video clips highlighting student thinking. We found that teachers' judgments were related to the quality of their discussions. Quantitative and qualitative analyses suggest that elaborated focus questions and interactions with colleagues may support teachers with relatively little physics teaching experience in using their collective wisdom to engage in a situation-specific skill necessary for responsive teaching. Highlights: We studied professional development using videos with evidence of student thinking. We examined the quality of teachers' discussions of video and resulting judgments. Quality of teachers' judgments was related to the quality of their discussions. Elaborated focus questions appear to support higher quality discussions. Working with colleagues appears to foster higher quality discussions and judgments.